Old Tunes, New Tones: (Re-)Defining the “Phanariot Verses” of the Greek Enlightenment - Chatzipanagioti-Sangmeister, Julia (The Historical Review/La Revue Historique, 2013)
Phanariot verses – poems and songs – of the eighteenth century and the first decades of the nineteenth comprise perhaps the largest segment of Modern Greek literature of the Age of the Enlightenment. This article calls into question the widely held view that Phanariot verses make up a homogenized body of texts. Based on extratextual and intratextual criteria and comparing texts from different periods of time, it proposes a distinction between two groups, an earlier one that relates to the Phanariot milieu and a more recent one that provided an outlet for expression for the fledgling Greek bourgeoisie.